2019
DOI: 10.1186/s41016-018-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of brain metastases: history and the present

Abstract: Brain metastases are significant causes of morbidity or mortality for patients with metastatic cancer. With the application of novel systematic therapy and improvement of overall survival, the prevalence of brain metastases is increasing. The paradigm of treatment for brain metastases evolved rapidly during the last 30 years due to the development of technology and emergence of novel therapy. Brain metastases used to be regarded as the terminal stage of cancer and left life expectancy to only 1 month. The appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 62 publications
0
47
0
4
Order By: Relevance
“…There has been relentless debate over the superiority of transcranial surgery or EVT for intracranial aneurysm. In a recent meta-analysis, Tsianaka et al [ 12 ] reported no superiority between transcranial surgery and EVT in the treatment of posterior circulation aneurysm. However, their report lacked a subgroup analysis for large posterior circulation aneurysms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been relentless debate over the superiority of transcranial surgery or EVT for intracranial aneurysm. In a recent meta-analysis, Tsianaka et al [ 12 ] reported no superiority between transcranial surgery and EVT in the treatment of posterior circulation aneurysm. However, their report lacked a subgroup analysis for large posterior circulation aneurysms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the endovascular era, many clinicians have advocated the use of EVT to treat posterior circulation aneurysm [ 6 , 9 , 12 ]. In our series, more than 60% of patients were treated by EVT, and the complete obliteration and post-treatment complication rates of EVT were comparable to those of transcranial surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment decision-making algorithm proposed during the COVID-19 pandemic is given in Figure 1. The suggested treatment options for brain tumours [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are enlisted in Table 1.…”
Section: Specific Scenariosmentioning
confidence: 99%
“…Brain metastases are the major cause of the poor prognosis and quality of life in all metastatic cancer patients 1 , 2 , especially in advanced non-small cell lung cancer (NSCLC) 3 . About 10-35% of the NSCLC patients have de novo BM on the diagnosis of lung cancer, and more than 50% of patients would develop BM during the treatment course 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%